Renewable Energies Resources Evaluation using a Geographic Information Systems in the Colombian Caribbean Region - Garcia, Gonzalo Romeno; Piero Rojas, Jhan; Castillo, Dora Villada (International Journal of Energy Economics and Policy, 2021)
This manuscript presents an integral evaluation of the use of wind and solar resources in the Colombian Caribbean region. For the use of solar and wind energy sources, spatial restrictions according to topography, natural parks, water reserves, indigenous and sacred reserves were taken into account. In addition, studies of the energy potential of wind and solar radiation were carried out through geostatistical analysis of different points in meteorological stations located in the region. Finally, areas with wind and solar potential were determined using the Geographic Information System for Renewable Energies (SIGER). The results show that the department of Guajira has the highest values of solar brightness (229-240 Month day), while the departments of Valledupar, Cesar, and part of Magdalena decrease in the range of 229 to 207 Month day. In terms of solar radiation, the departments of Guajira and AtlÃ¡ntico showed global solar radiation values of up to 6,015 W/m2. The departments of Cesar, Magdalena, and part of Bolivar showed values close to 5,259 W/m2; while Sucre, and Cordoba showed low solar radiation values of 4,502 W/m2. It is concluded that the departments of AtlÃ¡ntico and Guajira are excellent candidates for solar and wind energy projects due to their characteristics. The results of this manuscript are a fundamental basis for future technical-economic feasibility studies of renewable energy in the Colombian Caribbean region. In addition, it allows the elaboration of energy policies that encourage the execution of this type of study at a real level. Keywords: SIGER, renewable energies, solar energy, wind energy, wind potential JEL Classification: Q42 DOI: https://doi.org/10.32479/ijeep.11612